Membangun Jiwa Enterpreneurship dan Kreativitas di Sekolah Melalui Kegiatan Market Day Berorientasi Kearifan Lokal - Risna Dewi, Ni Wayan; Windayani, Ni Luh Ika; Arifin, Arifin; Laia, Bestari; Sutajaya, I Made (Cetta: Jurnal Ilmu Pendidikan, 2024)
Education is not only a place to gain conceptual and theoretical knowledge. But more than that, education must be able to provide practical things to students as part of the learning experience at school. This research aims to explore entrepreneurship-oriented education at Taman Tirta School, Mengwi, Bali, which has given birth to a market day program oriented to local Balinese wisdom as an effort to develop students' entrepreneurial spirit, creativity and responsibility through real experience in producing, marketing and selling. product or service. This research uses a descriptive method with a qualitative approach. Participants involved in this research included teachers, elementary and early childhood education students, education staff, and parents or guardians of students. Data collection methods used include interviews, observation and documentation. The data analysis technique in this research uses the Miles Huberman data analysis model with stages of data collection, data reduction, data presentation and drawing conclusions or verification. The conclusion is that the implementation of the market day program as part of entrepreneurship-oriented education at Taman Tirta School, Mengwi, Bali, provides various benefits for students, teachers, parents and the school environment as a whole. Through participation in market days, students learn about the production, marketing and sales processes of products, and have the opportunity to experience first-hand entrepreneurship. Apart from that, this program also creates awareness of environmental cleanliness and enthusiasm for sharing profits with those in need through the love sharing program.